Diagnostic and therapeutic problems in a case of mycosis fungoides diagnosed first as actinic reticuloid - Sokołowska-Wojdyło, Małgorzata; Roszkiewicz, Jadwiga; Zaucha, Jan Maciej; Barańska-Rybak, Wioletta; Ługowska-Umer, Hanna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Mycosis fungoides (MF) is one of the most frequent primary cutaneous lymphomas derived from peripheral T cells. In spite of its long lasting course, the disease is still a challenge for dermatologists, oncologists and haematologists because of the lack of effective therapeutic methods in late stages of this lymphoma. Objective. To present diagnostic and therapeutic difficulties in a case of MF. Case report. The patient, a 72-year-old woman, was observed in our department from October 2007 to September 2009 with melanoerythrodermic skin lesions which were inconsistent histopathologically with mycosis fungoides. The patient was treated for drug eruption and actinic reticuloid. The diagnosis of MF was established after 19 months of observation. At that time erythematous and infiltrated lesions developed and histopathological examination was of MF type.